Cirurgia de redesignação sexual para mulheres trans: Perspectivas do campo biomédico e jurídico - Toni Junior, Claudio Noel de (2024)
Gender issues have always raised the curiosity of others, who want to know the differences that do (or do not) exist in non-binary bodies, the ones not identified according to the male-female logic. Until recently, little was known about the differentiation of gender, with trans people being often confused with intersex/hermaphrodite people. Also lacking was the medical will to decide what someone's true sex was, based on possibilities other than the subject's own self-determination; the former was also deeply enmeshed with two other types of powers - juridical and medical powers - when it comes to determining what is normal and acceptable sexuality. This discursive/normative concertation has been challenged by the emergence of identity movements, which, in communion with the struggles with other social movements, such as the feminist movement and the black movement, have gained force for the visibility of the LGBTQIAPN+ movement and for the dissemination of its struggles, both globally and nationally, in favor of the recognition of rights to autonomy and human dignity. This, in turn, has put pressure on decision-making mechanisms towards their inclusion in public policies, and towards the recognition of their own existence and even the preservation of their lives, especially shaped by the possibility of sexual reassignment in their physical and civil forms. In this context, the problem of being transsexual in the world today emerges, in such a way that the struggle unfolds in different scenarios, and that is the theme of this work, bringing together the theoretical-reflective contributions with which we seek to build, with an interdisciplinary perspective with the aid of Science, Technology and Society, elements that support the necessary reflection on the issues of being transsexual, aiming to contribute to the achievement of the goals of the trans population, especially those most vulnerable.